Antifouling wear-resistant auxiliary agent as well as preparation method and application thereof

By using nano-silica hybrid multi-branched polymers containing perfluoropolyether groups, an anti-fouling and wear resistance additive with a multi-branched structure is solved, and the problems of poor controllability of the preparation process, difficult raw materials, poor wear resistance and compatibility in the prior art are solved, and the anti-fouling and wear resistance of UV cured coatings are significantly improved.

CN119684543AActive Publication Date: 2025-03-25JUHUA GROUP TECH CENT

Patent Information

Application Number
CN202411939334.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-25
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

In the prior art, the preparation process of anti-fouling and wear-resistant additives is poorly controlled, the raw materials are not easily obtained, and the wear resistance and compatibility are poor, making it difficult to effectively improve the anti-fouling and wear resistance in the UV cured coating system.

Method used

Using a nano-silica hybrid multi-branched polymer containing perfluoropolyether groups, the nano-silica with hydroxyl groups and the monoisocyanate containing unsaturated bonds is formed by reacting a single-ended active perfluoropolyether alcohol with isophorone diisocyanate, combining nano-silica with hydroxyl groups on the surface and monoisocyanate containing unsaturated bonds to form a multi-branched structure antifouling and wear-resistant additive.

Benefits of technology

It significantly improves the anti-fouling, anti-fingerprint characteristics and wear resistance of the coating surface, enhances compatibility with the UV coating system, and is easy to obtain raw materials and has little difficulty in process control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212239490000031
    Figure BDA0005212239490000031
  • Figure BDA0005212239490000032
    Figure BDA0005212239490000032
  • Figure BDA0005212239490000041
    Figure BDA0005212239490000041
Patent Text Reader

Abstract

The invention discloses an antifouling wear-resistant auxiliary agent and a preparation method and application thereof, and belongs to the technical field of fluorine-containing functional preparations, the antifouling wear-resistant auxiliary agent is prepared from the following raw materials by mole: 1-2 parts of single-ended active perfluoropolyether alcohol PFPE-OH; 1 to 2 parts of isophorone diisocyanate; 1 part of nano silicon dioxide containing hydroxyl groups on the surface; 2 to 5 parts of monoisocyanate containing unsaturated bonds; 2 to 25 parts of acrylic acid hydroxyl ester; 40 to 400 parts of a comonomer; 2-20 parts of a reaction active monomer; the reactive monomer contains an unsaturated bond and is used for side chain grafting. The antifouling wear-resistant auxiliary agent comprises a nano silicon dioxide hybrid multi-branched polymer containing a perfluoropolyether group, contains a plurality of unsaturated sites, is suitable for a UV curing coating system, and can significantly improve the antifouling and anti-fingerprint characteristics and wear resistance of the surface of a coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fluorine-containing functional preparations, and in particular to an antifouling and wear-resistant additive and a preparation method and application thereof. Background Art

[0002] Ultraviolet (UV)-cured coatings are hard coatings formed by the rapid curing and cross-linking of active monomers in the coating by photoinitiators under the irradiation of ultraviolet light. UV-cured coatings have the advantages of fast curing speed, green environmental protection, low energy consumption, good adhesion, high coating quality, and good durability. Therefore, they are widely used in the fields of electronics, automobiles, medical care, and packaging. In smartphones, tablet computers, and optical displays, UV coatings are often used as key display interface materials. However, they are easily attached with impurities such as fingerprints, sebum, and sweat, which affects the user experience. In addition, wear resistance is also one of its key technical indicators. Therefore, it is necessary to develop anti-fouling and wear-resistant additives to improve the anti-fouling and wear resistance of UV-cured coatings.

[0003] The method to improve the antifouling property of the coating is generally to add low surface tension substances (such as fluorine-containing or silicon-containing functional additives, etc.) to reduce the surface energy of the coating, or to change the surface microstructure of the coating to directly improve the antifouling property; obviously, the method of adding low surface tension substances to improve the antifouling property of the coating is more efficient and easy to implement. Perfluoropolyether antifouling agents are widely used antifouling additives in recent years, but due to their high fluorine content, they have poor compatibility with other components in the coating, resulting in component separation, which in turn deteriorates the surface performance. The use of long-chain fluoroalkyl side chains can significantly improve the surface antifouling properties, but the coating surface has poor smoothness, which affects the product experience. Double-ended perfluoropolyether can solve the problems of compatibility and smoothness, but the raw materials are not easy to obtain, making it difficult to achieve widespread use.

[0004] Patent document with publication number CN118440292A discloses an acrylic compound containing a perfluoropolyether group, which has a central structural unit of two arylene skeletons connected by a carbodiimide group, wherein the perfluoropolyether group is bonded to one end via a carbamate bond and the multifunctional (meth)acryloyl group is bonded to the other end via a carbamate bond; the acrylic compound is soluble in common solvents and can give the coating a good initial contact angle and wear resistance. The reaction mechanism of the invention is the reaction of alcohol hydroxyl group and polyisocyanate to form carbamate, and it is inevitable that the perfluoropolyether chain segments are bonded to multiple ends at the same time, which makes the structure difficult to control.

[0005] The patent document with publication number CN115612031A discloses a thermosetting antifouling additive, which is a high molecular polymer with carbon-carbon as the main chain, and contains perfluoropolyether groups and hydroxyl groups in its side chains, and the fluorine content does not exceed 40.0%, the hydroxyl value is not less than 17.5mg KOH / g, and the molecular weight of the perfluoropolyether group is not less than 800g / mol. The additive is soluble in non-halogen ester ketone alcohol benzene solvents and has excellent compatibility with hydroxyl acrylic resin and thermosetting coatings. The antifouling additive has a good effect when applied to thermosetting coating systems, but when added to UV curing systems, the wear resistance is greatly reduced due to the lack of fixed anchor points, affecting the surface state of the coating.

[0006] Patent document with publication number CN105482680A discloses a UV-curable hyperbranched perfluoropolyether polyurethane acrylate coating, which contains a hyperbranched perfluoropolyether polyurethane acrylate oligomer, which is obtained by reacting a hyperbranched fluorinated polyester obtained by reacting a perfluoropolyether acyl chloride with a hyperbranched polyester, and then reacting with polyisocyanate and (methyl) acrylate. The corresponding reaction also has the probability of generating a double-terminal fluorinated hyperbranched polyester, and the reaction activity of the acyl chloride and the hydroxyl group is extremely high, and the reaction is difficult to control; on the one hand, the hyperbranched perfluoropolyether polyurethane acrylate oligomer may affect the compatibility with the UV coating system due to the high fluorine content, and on the other hand, there may be insufficient crosslinking with the active monomer in the UV coating system, affecting the wear resistance of the coating.

[0007] Therefore, it is necessary to develop new single-ended perfluoropolyether-based antifouling and wear-resistant additives for UV-curing coating systems. Summary of the invention

[0008] In order to solve the problems in the prior art of poor controllability of the preparation process of anti-fouling and wear-resistant additives, difficulty in obtaining raw materials, poor wear resistance and compatibility, the present invention provides an anti-fouling and wear-resistant additive, which includes a nano-silica hybrid multi-branched polymer containing a perfluoropolyether group and containing multiple unsaturated sites, is suitable for UV-curing coating systems, and can significantly improve the anti-fouling, anti-fingerprint and wear resistance of the coating surface.

[0009] The specific technical solutions adopted are as follows:

[0010] An antifouling and wear-resistant additive, which is made of the following raw materials in terms of molar fractions:

[0011]

[0012]

[0013] Among them, the relative density of nano-silicon dioxide containing hydroxyl groups on the surface is 2.3-3.5g / cm3 The reactive monomer contains an unsaturated bond, including a vinyl monomer or an acrylate, which is used for side chain grafting.

[0014] Preferably, the antifouling and wear-resistant additive is made of the following raw materials in molar fractions:

[0015]

[0016] Specifically, the single-end active perfluoropolyether alcohol PFPE-OH can be selected from K-type, Y-type, Z-type or D-type single-end active perfluoropolyether alcohol.

[0017] Preferably, the weight average molecular weight of the single-end active perfluoropolyether alcohol PFPE-OH is 500-5000 g / mol. Too high molecular weight may affect the solubility of the antifouling and wear-resistant additive in UV coatings and solvents, and premature precipitation may cause coating leveling, haze, whitening and other defects; too low molecular weight has a greater impact on antifouling properties.

[0018] Preferably, the average particle size of the nano-silicon dioxide containing hydroxyl groups on the surface is 15-35nm. If the particle size is too large, there will be too many active sites, the probability of multi-fluorine chain bonding will increase, and the compatibility will deteriorate; if the particle size is too small, there will be too few active sites, making it difficult to form the antifouling and wear-resistant additive.

[0019] The monoisocyanate containing unsaturated bonds includes ethyl isocyanate acrylate, vinyl isocyanate or allyl isocyanate.

[0020] The hydroxy acrylate is at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate.

[0021] The comonomer is selected from at least one of methyl acrylate, methyl methacrylate, n-butyl acrylate, n-butyl methacrylate, dodecyl acrylate, dodecyl methacrylate, tetradecyl acrylate, tetradecyl methacrylate, octadecyl acrylate, octadecyl methacrylate, vinyl acetate and styrene.

[0022] The reactive monomer is selected from one or more of ethyl isocyanate acrylate, vinyl isocyanate or allyl isocyanate.

[0023] The antifouling and wear-resistant additive has strong universality, is soluble in conventional solvents and a variety of UV light-curing coating systems, and can also be used in other types of coating systems, such as thermal curing coating systems. The introduction of the antifouling and wear-resistant additive into the coating system, especially into the UV light-curing coating system, can significantly improve the antifouling and anti-fingerprint properties and wear resistance of the coating surface.

[0024] The present invention also provides a method for preparing the antifouling and wear-resistant additive, comprising the following steps:

[0025] (1) single-end active perfluoropolyether alcohol PFPE-OH is reacted with isophorone diisocyanate to obtain single-end perfluoropolyether urethane;

[0026] (2) using single-ended perfluoropolyether carbamate to react with nano-silica containing hydroxyl groups on the surface to obtain a hybrid fluorine-containing nano-silica intermediate;

[0027] (3) using the hybrid fluorine-containing nano-silica intermediate to react with a monoisocyanate containing an unsaturated bond to introduce an unsaturated bond into the hybrid fluorine-containing nano-silica intermediate;

[0028] (4) using the hybrid fluorine-containing nano-silica intermediate with unsaturated bonds obtained in step (3) to react with hydroxy acrylate and comonomer to obtain a polymer intermediate;

[0029] (5) The polymer intermediate is reacted with a reactive monomer to graft the reactive monomer onto the side chain of the polymer intermediate to obtain the antifouling and wear-resistant additive.

[0030] Taking isophorone diisocyanate, ethyl isocyanate acrylate, hydroxyethyl acrylate and methyl methacrylate as examples, the reaction equation of the present invention is shown below:

[0031]

[0032]

[0033] Preferably, the preparation method of the antifouling and wear-resistant additive specifically comprises the following steps:

[0034] S01: weigh single-end active perfluoropolyether alcohol PFPE-OH and isophorone diisocyanate in proportion, dissolve them in 1-2 times the weight of heptafluorocyclopentane, add 300-500ppm of catalyst dibutyltin dilaurate based on the weight of the reactants, and heat to 35-50°C under inert gas protection for 3-6h to obtain a single-end perfluoropolyether urethane solution;

[0035] S02 weighs nano-silica containing hydroxyl groups on the surface according to a certain proportion, disperses it in the solution obtained in S01, and continues to react for 3-10 hours under the protection of an inert gas to obtain a hybrid fluorine-containing nano-silica intermediate solution;

[0036] S03, dropwise adding a corresponding amount of monoisocyanate containing an unsaturated bond (e.g., ethyl isocyanate acrylate) to the solution obtained in S02, and continuing the reaction under the protection of an inert gas for 3-6 hours to introduce an unsaturated bond into the hybrid fluorine-containing nano-silica intermediate, and performing reduced pressure distillation to obtain a viscous hybrid fluorine-containing nano-silica intermediate with an unsaturated bond;

[0037] S04: weigh hydroxy acrylate, comonomer and 1-3 times the weight of ethyl acetate solvent in proportion, heat to 60-85°C under inert gas protection, add 0.5-3% of azobisisobutyronitrile based on the total monomer content, and slowly drop the hybrid fluorine-containing nano-silica intermediate with unsaturated bonds obtained in S03 for 0.5-2h, then continue to react for 2-4h and then cool to obtain a polymer intermediate solution;

[0038] S05: add reactive active monomers to the polymer intermediate solution obtained in S04, and at the same time add 200-400ppm of catalyst dibutyltin dilaurate, heat to 35-50°C under inert gas protection, react for 3-6h, and then separate to obtain antifouling and wear-resistant additive, and then add isopropanol to adjust the effective ingredient to 20% for later use.

[0039] Specifically, in step (1), since the activity of the isocyanate groups on the side chains of isophorone diisocyanate is three times that of the isocyanate groups on the aliphatic ring, it can be controlled to react only with the isocyanate groups on the side chains during the reaction with perfluoropolyether alcohol, without participating in the reaction of the isocyanate groups on the aliphatic ring, thereby greatly reducing the difficulty of the process technology and making it controllably a single-chain antifouling and wear-resistant additive.

[0040] In step (2), the nano-silica containing hydroxyl groups on the surface has multiple hydroxyl reaction sites, which can react with the isocyanate groups on the aliphatic ring in the single-ended perfluoropolyether urethane generated in the first step. Due to the steric hindrance of its three-dimensional structure and the large difference in solubility with fluorine-containing molecules, the excessive addition of nano-silica in the reaction can relatively simply control the connection of a single fluorine-containing chain segment to a single silica microsphere. The excess nano-silica can continue to react backward to finally generate a nano-silica hybrid polymer molecule that does not contain fluorine and contains multiple organic chains. It can also be used as a multi-claw active monomer to improve the cross-linking density and wear resistance and aging resistance.

[0041] Furthermore, the polymer chain segments formed by hydroxy acrylate and reactive monomers can form a structure similar to a stem around the hybrid fluorine-containing nano-silica intermediate, thereby forming a multi-branched structure with a perfluoropolyether chain segment at one end and an organic polymer chain segment at multiple ends, which can not only be dissolved in non-fluorine-containing solvents, but also has excellent compatibility with the active monomers in the UV coating system. And this multi-branched structure has good fluidity and strong mobility. During the film-forming process, it can quickly follow the fluorine-containing chain segment to move upward, which is helpful for anti-fouling and wear-resistant properties. And the polymer chain segment contains multiple hydroxyl groups (generated by hydroxyl-containing acrylate monomers), which can provide reactive groups for the next step of unsaturation.

[0042] The invention also provides application of the antifouling and wear-resistant additive in the preparation of coatings.

[0043] Preferably, the coating is a UV light-curing coating, and the amount of the antifouling and wear-resistant additive added is 0.5-5wt%, preferably 0.1-3wt%, based on the weight of the UV light-curing coating.

[0044] When the antifouling and wear-resistant additive is added to the UV coating to form a film, its extremely low surface tension drives the entire structure upward toward the air and is located in the outermost layer, thereby exhibiting excellent smoothness and antifouling properties. Due to its flexible chain structure, it can stretch with external forces during the initial wear resistance process, and has a synergistic effect on wear resistance.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The antifouling and wear-resistant additive provided by the present invention has good compatibility with the coating system. The antifouling and wear-resistant additive comprises a nano-silicon dioxide hybrid multi-branched polymer containing a perfluoropolyether group. The multi-branched structure significantly improves the compatibility, and the antifouling and wear-resistant additive can also provide multiple cross-linking sites to improve the antifouling durability of the coating system (especially UV light-curing coating);

[0047] (2) The antifouling and wear-resistant additive provided by the present invention has good surface antifouling effect. The antifouling and wear-resistant additive is a multi-branched dendritic fluorine-containing hybrid structure. When forming a film, due to the self-stratification effect of the fluorine-containing segment, the perfluoropolyether segment is directed upward into the air, and the hybridized nano-silica is located in the upper layer to form a nano-scale micro-convex structure. The downward side is a polymer side chain containing multiple unsaturated bonds that can be cross-linked with the monomer in the coating or can be dissolved in the solvent. It is fixed in the coating like a rhizome-like cross-linking, thereby fixing the surface conformation. The obtained coating has good and stable surface antifouling properties.

[0048] (3) The antifouling and wear-resistant additive provided by the present invention can significantly improve the wear resistance of the coating. The introduction of nano-silicon dioxide helps to improve the wear resistance and aging resistance of the UV coating, and the synergistic multi-branch cross-linking curing sites increase the cross-linking density, thereby reducing physical damage and friction during use.

[0049] (4) The raw materials of the anti-fouling and wear-resistant additive of the present invention are easy to obtain, and the difficulty of process control in the preparation method is small. The present invention uses single-end active perfluoropolyether alcohol PFPE-OH to react with isophorone diisocyanate, and then hybridizes with nano-silica containing hydroxyl groups on the surface. The difference in the activity of the isocyanate group can achieve precise control of the bonding of single-chain perfluoropolyether, avoiding the disorder of process control and the generation of polyfluoro chains. It has excellent selectivity and achieves the effect of single-molecule fluorine-containing single chain of the anti-fouling and wear-resistant additive of the present invention, which is more suitable for industrial production. DETAILED DESCRIPTION

[0050] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description through specific embodiments. In the following description, many specific details are set forth in order to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0051] The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The contents not described in detail in this specification belong to the prior art known to professionals in the field.

[0052] Examples 1-6, Comparative Examples 1-4

[0053] Specifically, the raw materials for preparing the anti-fouling and wear-resistant additives of the embodiments and comparative examples are shown in Table 1; the preparation method of the anti-fouling and wear-resistant additive comprises the following steps: S01 weighing single-end active perfluoropolyether alcohol PFPE-OH and isophorone diisocyanate according to the proportions in the table below, dissolving them in heptafluorocyclopentane, adding 500ppm of the catalyst dibutyltin dilaurate based on the weight of the reactants, heating to 50°C for reaction for 5h under the protection of inert gas, and obtaining a single-end perfluoropolyether urethane solution; S02 weighing nano-silica containing hydroxyl groups on the surface according to the proportion, dispersing it in the solution obtained in S01, and continuing to react for 5h under the protection of inert gas to obtain a hybrid fluorine-containing nano-silica intermediate solution; S03 dropping a corresponding amount of monoisocyanate containing unsaturated bonds into the solution obtained in S02, and continuing to react for 4h under the protection of inert gas. An unsaturated bond is introduced into the hybrid fluorine-containing nano-silica intermediate, and a viscous hybrid fluorine-containing nano-silica intermediate with an unsaturated bond is obtained by vacuum distillation; S04: hydroxy acrylate, comonomer and ethyl acetate solvent are weighed in proportion, mixed, heated to 60°C under inert gas protection, 2% of azobisisobutyronitrile of the total monomer content is added, and the hybrid fluorine-containing nano-silica intermediate with an unsaturated bond obtained in S03 is slowly dripped for 1 hour, and then the reaction is continued for 3 hours and then the temperature is lowered to obtain a polymer intermediate solution; S05: reactive active monomers are dripped into the polymer intermediate solution obtained in S04, and 300 ppm of catalyst dibutyltin dilaurate can be added at the same time. The temperature is raised to 50°C under inert gas protection for reaction for 6 hours, and then an antifouling and wear-resistant additive is separated, and isopropanol is added to adjust the effective ingredient to 20% to obtain an antifouling and wear-resistant additive solution.

[0054] Table 1 Preparation raw material composition of examples and comparative examples (parts by mole fraction)

[0055]

[0056] Performance Testing

[0057] (1) UV coating configuration and coating preparation

[0058] Table 2 Typical configuration of UV coatings

[0059]

[0060] (2) The film-forming process of the antifouling and wear-resistant coating is as follows: the prepared UV coating is sprayed onto the PC board with a wet film thickness of 15-25 μm, then dried at 65°C for 5 min, and then cured by irradiation with a 60W high-pressure mercury lamp with an irradiation energy of 2.5 J / cm 2 The irradiation time is 10-15s, and the coating performance is tested on the cured PC coating sample.

[0061] (3) Test methods and test standards

[0062] ① Solubility test: Add 2 parts by mass of the antifouling and wear-resistant additive prepared in the embodiment or comparative example to 8 parts by mass of the solvent, disperse for more than 20 minutes to ensure full dissolution, and then place for more than 24 hours to observe whether there is stratification or precipitation. No stratification, precipitation and transparency indicate solubility, which is indicated by ◎, no precipitation, no stratification but not completely transparent, which is indicated by ○, otherwise it indicates poor solubility, which is indicated by ×.

[0063] ② Antifouling test: Determination of water contact angle. The contact angle of the prepared UV coating sample was tested using Shanghai Zhongchen JC2000 D1 dynamic contact angle measuring instrument, and the test method was GB / T24368. Deionized water was used as the test liquid, and the test should be carried out at a temperature of (25±2)℃. One sample should be tested three times for one test liquid, and the average value was taken. A water contact angle exceeding 115° is indicated as A, 110-115° is indicated as B, and ≤110° is indicated as C.

[0064] ③ Wear resistance test 1: The obtained UV coating was subjected to a steel wool wear test according to RIM WI-QMR-06-002 standard. On a Taber 5700 linear wear tester (Taber Industrial Manufacturing), 0000# steel wool was used and the contact area was 2cm*2cm under a load of 1000g. The coating surface was rubbed at a cycle speed of 50 times / minute, a friction length of 5.0 cm, and a friction number of 2000 times. The water contact angle of the coating surface after friction is ≥105°, which is indicated as OK, ≥100° is indicated as √, <100° is indicated as ×, and <90° is indicated as ××.

[0065] ④Abrasion resistance test 2: The obtained UV coating was subjected to a steel wool abrasion resistance test according to RIM WI-QMR-06-002 standard, on a Taber 5700 linear abrasion tester (Taber Industrial Manufacturing), using a polyester fiber WIP-1009LE dust-free cloth folded in three layers, with a contact area of ​​1cm*1cm, a load of 500g, a cycle speed of 50 times / min, a friction length of 5.0cm, and a friction number of 3000 times. The water contact angle of the coating surface after friction is ≥105°, which is indicated as OK, ≥100° is indicated as √, and <100° is indicated as ×.

[0066] The test results of an antifouling and wear-resistant additive and a coating prepared according to the embodiments and comparative examples of the present invention are shown in the following table:

[0067] Table 3 Solubility test results

[0068]

[0069] Table 4 Coating performance test results

[0070] Example Antifouling Wear resistance 1 Wear resistance 2 Example 1 A OK OK Example 2 B √ √ Example 3 A OK OK Example 4 A OK OK Example 5 A OK OK Example 6 A OK OK Comparative Example 1 B × × Comparative Example 2 A ×× ×× Comparative Example 3 B × × Comparative Example 4 C X X

[0071] It can be seen from the performance test of the comparative example that the nano-silica of the fluorine-containing chain segment in comparative example 1 is connected to multiple isocyanoethyl acrylates, forming a root-like anchoring structure directly connected to the nano-silica, and there is no branched polymer chain segment, resulting in poor compatibility with conventional solvents, poor compatibility with UV coating systems, and easy to precipitate in advance, resulting in opacity of the coating and uneven antifouling of the coating surface; comparative example 2 does not have the last step of isocyanoethyl acrylate bonded, and at this time, there is no cross-linking point with the UV coating active monomer in the antifouling and wear-resistant additive, and it is difficult to anchor on the surface, so the surface antifouling, that is, the water contact angle is high and the wear resistance is poor. There is no hybridization of nano-silica in comparative example 3, so a structure with perfluoropolyether at one end and an organic polymer chain at the other end is formed. The molecules of this structure have poor compatibility in common solvents and are easy to precipitate in advance. Due to the lack of the synergistic effect of the micro-convex structure of nano-silica, the water contact angle is not ideal and the wear resistance is also unsatisfactory. Comparative Example 4 does not add the fluorine-containing segment of perfluoropolyether, thus forming a multi-branched dendritic structure without fluorine, which can be used as an active monomer in UV coatings. However, since it does not contain fluorine element, its water contact angle and wear resistance are poor.

[0072] In summary, the antifouling and wear-resistant additive provided by the present invention comprises a nano-silicon dioxide hybrid multi-branched polymer containing a perfluoropolyether group, and the hybrid polymer contains multiple unsaturated sites, which is suitable for UV curing coating systems and significantly improves the antifouling and anti-fingerprint properties and wear resistance of the coating surface. The coating system of the antifouling and wear-resistant additive of the present invention has strong universality and is soluble in conventional solvents and a variety of UV coating systems.

[0073] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An antifouling and wear-resistant additive, characterized in that: The antifouling and wear-resistant additive is made of the following raw materials in terms of molar fractions: Among them, the relative density of nano-silicon dioxide containing hydroxyl groups on the surface is 2.3-3.5g / cm 3 The reactive monomer contains an unsaturated bond and is used for side chain grafting.

2. The antifouling and wear-resistant additive according to claim 1, characterized in that: Made from the following raw materials in molar fractions:

3. The antifouling and wear-resistant additive according to claim 1, characterized in that: The single-end active perfluoropolyether alcohol PFPE-OH can be selected from K-type, Y-type, Z-type or D-type single-end active perfluoropolyether alcohol, and the weight average molecular weight is 500-5000 g / mol.

4. The antifouling and wear-resistant additive according to claim 1, characterized in that: The average particle size of the nano-silicon dioxide containing hydroxyl groups on the surface is 15-35 nm.

5. The antifouling and wear-resistant additive according to claim 1, characterized in that: The monoisocyanate containing unsaturated bonds includes ethyl isocyanate acrylate, vinyl isocyanate or allyl isocyanate.

6. The antifouling and wear-resistant additive according to claim 1, characterized in that: The hydroxy acrylate is at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate; and / or the comonomer is at least one of methyl acrylate, methyl methacrylate, n-butyl acrylate, n-butyl methacrylate, dodecyl acrylate, dodecyl methacrylate, tetradecyl acrylate, tetradecyl methacrylate, octadecyl acrylate, octadecyl methacrylate, vinyl acetate, and styrene; and / or the reactive monomer is at least one of isocyanate ethyl acrylate, vinyl isocyanate, or allyl isocyanate.

7. The method for preparing the antifouling and wear-resistant additive according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) single-end active perfluoropolyether alcohol PFPE-OH is reacted with isophorone diisocyanate to obtain single-end perfluoropolyether urethane; (2) using single-ended perfluoropolyether carbamate to react with nano-silica containing hydroxyl groups on the surface to obtain a hybrid fluorine-containing nano-silica intermediate; (3) using the hybrid fluorine-containing nano-silica intermediate to react with a monoisocyanate containing an unsaturated bond to introduce an unsaturated bond into the hybrid fluorine-containing nano-silica intermediate; (4) using the hybrid fluorine-containing nano-silica intermediate with unsaturated bonds obtained in step (3) to react with hydroxy acrylate and comonomer to obtain a polymer intermediate; (5) The polymer intermediate is reacted with a reactive monomer to graft the reactive monomer onto the side chain of the polymer intermediate to obtain the antifouling and wear-resistant additive.

8. Use of the antifouling and wear-resistant additive according to any one of claims 1 to 6 in the preparation of coatings.

9. The use of the antifouling and wear-resistant additive according to claim 8 in the preparation of coatings, characterized in that: The coating is a UV light-curing coating, and the amount of the antifouling and wear-resistant additive added is 0.5-5wt% based on the weight of the UV light-curing coating.

Citation Information

Patent Citations

  • Ultraviolet light polymerization hyperbranched perfluoropolyether urethane acrylate coating

    CN105482680A

  • Thermocuring antifouling additive

    CN115612031A

  • Acrylic compound containing perfluoropolyether group and composition containing same

    CN118440292A

  • Anti-soiling composition, anti-soiling film, anti-soiling laminated film, transfer film, and resin laminate, and method for manufacturing resin laminate

    CN102459378A

  • Additive for non-stick coatings

    CN107523153A

Cited By

  • Fluorine-containing material for dual-curing system coating as well as preparation method and application of fluorine-containing material

    CN120665517A

  • Perfluoropolyether-terminated polymer, electrolyte, battery, preparation method and application

    CN121270937A